Pengelolaan Persediaan Obat Pada Apotek Adli Banjarmasin - Farah Hanna; Putriana Salman; Rizky Amelia (Indonesian Journal of Applied Accounting and Finance, 2024)
The most appropriate method chosen by the company must be in line with the needs and condition of the company. The purpose of this research is to examine the inventory management at Adli Pharmacy Banjarmasin using the FIFO-Perpetual method. The problem addressed in this study is that the inventory purchased and sold has not been managed well and consistently in terms of recording, valuation, and presentation in financial statements. The research employed a descriptive quantitative method. The results of the study indicate that by implementing inventory management, the inventory amount can be known in real-time without performing physical counts first. The implication of this research is that the company can implement inventory management that consists of consistent recording, measurement, and presentation of the inventory, thus facilitating business decision-making.